Thoroughbred stallion fertility is significantly associated with FKBP6 genotype but not with inbreeding or the contribution of a leading sire. (5th October 2021) - Castaneda, C.; Juras, R.; Kjöllerström, J.; Hernandez Aviles, C.; Teague, S. R.; Love, C. C.; Cothran, E. G.; Varner, D. D.; Raudsepp, T.
Summary: This is a follow‐up study to validate the previously detected association of the FKBP6 gene with stallion subfertility. Using a select cohort of 150 Thoroughbred stallions with detailed breeding records, we confirm significant association ( P  < 0.0001) between low per‐cycle pregnancy rates (≤50%) and a combined A/A–A/A genotype of SNPs chr13:11 353 372G>A and chr13:11 353 436A>C in FKBP6 exon 5. We also show that stallion subfertility and the combined genotype A/A–A/A are not associated with the level of genetic diversity based on 12 autosomal microsatellite markers, or with pedigree‐based inbreeding rate, or the extent of contribution of a leading Thoroughbred sire, Northern Dancer, in a stallion's pedigree. We develop a TaqMan allelic discrimination assay for the two SNPs to facilitate accurate and high‐throughput genotyping. We determine allele, genotype and combined genotype frequencies of FKBP6 exon 5 SNPs in a global cohort of 518 Thoroughbreds (76% stallions or geldings and 24% mares) and show that the frequency of the A/A–A/A genotype is 4%. Because there is no similar association between the FKBP6 exon 5 genotype and stallion subfertility in Hanoverians, we suggest that the two SNPs are not causative but rather tagging a breed‐specific haplotype with genetic variants unique to Thoroughbreds. Further WGS‐based research is needed to identify the molecular causes underlying the observed genotype–phenotype association in Thoroughbred stallions.